重新思考华族文化意识：从新加坡《华文伴我行》课本解析文化传承 = (Re)thinking ethnic Chinese cultural consciousness: an analysis of cultural transmission in Singapore’s “Hua Wen Ban Wo Xing” textbooks - 許馨云 Koh, Rachel Xin Yun (Nanyang Technological University, 2025)
在重新思考华族文化意识和避免文化失根时，华文教育中具有“文以载道”功能的课本肩 负着传承和捍卫的任务。目前有关新加坡华文教材的研究注重在语言学、文学和教育学， 而对华文课本内容与文化意识之间的关系尚缺分析。因此，本文以最新版的中学《华文伴 我行》课本的华族文化内容为研究对象来弥补这个研究欠缺。通过量化和定性的研究方法， 本文旨在为新加坡华文教育中的华族文化元素提供新视角。本文发现《华文伴我行》拥有 多元的华族文化主题和元素，而内容也注重在华族传统文化和新加坡本土化的华族文化。 有些课文也呈现多个文化元素、以隐性的方式呈现别的文化元素，而有些课文的文化内容 只占了课文的一部分。再加上，课文的图片、词汇和名句、课文类型和附加练习的再现都 让学生以真实和实用性的方式与文化建立连结，提升文化理解。为此，《华文伴我行》在 广泛的华族群体之间建立桥梁，让共同的文化叙事强化群体认同。它也见证了华族文化意 识的捍卫和推崇，从而避免断根。 In (re)thinking ethnic Chinese cultural consciousness and preventing the loss of cultural “roots”, textbooks in Chinese language education serve as vital tools in promoting and preserving Chinese culture. Currently, studies on Singapore Chinese textbooks focus on linguistics, literature and educational theories, with limited attention paid to the relationship between Chinese textbooks contents and ethnic Chinese cultural consciousness. This paper addresses the gap by analysing the cultural contents in the newest secondary school Chinese textbooks “Hua Wen Ban Wo Xing”. Quantitative and qualitative research methods are utilised in this study to achieve the aim of providing new perspectives on ethnic Chinese cultural elements in Singapore’s Chinese language education. The findings show that the themes and elements of the texts are multifaceted and includes both traditional and localised Chinese culture. Furthermore, some texts incorporated multiple cultural themes and elements, some texts present cultural elements implicitly, and the cultural content in some texts only make up a portion of the text. The images, vocabulary and phrases used, types of texts and supplementary exercises also enables students to connect with Chinese culture through authentic and practical applications, which demonstrably enhances their cultural understanding. This study suggests that textbooks build connections between individuals in the broader ethnic Chinese community, reinforcing group identity through shared narratives. As such, textbooks play an indispensable role in maintaining and fostering cultural consciousness and preventing “rootlessness”.